Safety and Efficacy of Vaccination During Lactation: A Comprehensive Review of Vaccines for Maternal and Infant Health Utilizing a Large Language Model Citation Screening System - Sien J. Mulleners; Hannah G. Juncker; Jan Zuiderveld; Kirsten A. Ziesemer; Johannes B. van Goudoever; Britt J. van Keulen (Vaccines)
Newborns are born with an immature immune system, making them susceptible to infections early in life. Human milk provides essential nutrients and immunological factors that support infant immunity. Maternal vaccination during lactation has the potential to enhance these benefits by triggering an immune response in the mother, potentially extending protection to her child. However, lactating individuals are often excluded from vaccine trials, leading to uncertainties about vaccine safety and efficacy during the postpartum period. This study critically evaluates the effectiveness of vaccines in enhancing the immune-supporting properties of human milk and assesses their safety and efficacy for lactating mothers and their infants. By examining potential benefits alongside safety concerns, we aim to provide a comprehensive understanding of postpartum vaccination’s impact on maternal and infant health. We utilized large-language models (LLMs) to enhance the review process and performed a structured literature search across Ovid/Medline, Embase, and Clarivate Analytics using terms like “breastfeeding”, “postpartum”, and “vaccination”. A three-stage screening process involving human and LLM-assisted evaluation focused on postpartum vaccines and their implications for maternal and infant health. We identified 73 studies covering vaccines against COVID-19, cholera, influenza, pertussis, pneumococcal, rabies, polio, rotavirus, rubella, varicella, typhoid, smallpox, and yellow fever. Most vaccines, such as those for COVID-19 and influenza, appear safe and effective for postpartum use without requiring precautionary measures. However, caution is advised with vaccines such as the yellow fever vaccine, where temporary breastfeeding cessation is recommended. Overall, this review underscores the compatibility of most vaccines with lactation and suggests its benefits for both mother and infant.